Effect of Select Tannin Sources on Pathogen Control and Microbial Nitrogen Metabolism in Composted Poultry Litter Intended for Use as a Ruminant Crude Protein Feedstuff - Arzola-Alvarez, Claudio; Anderson, Robin C.; Hume, Michael E.; Ledezma, Evelyn; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Arzola-Rubio, Alejandro; Ontiveros-Magadan, Marina; Min, Byeng Ryel; Wottlin, Lauren R.; Copado, Ramon; Salinas-Chavira, Jamie (Frontiers in Veterinary Science, 2022)
Poultry litter is a good crude protein supplement for ruminants but must be treated to kill pathogens before feeding. Composting effectively kills pathogens but risks loss of ammonia due to uric acid degradation. Because tannins possess antimicrobial activity and can inhibit uric acid metabolism, we tested their ability to preserve uric acid and reduce pathogens during poultry litter composting. In two experiments, poultry litter was mixed with phosphate buffer and distributed to 50-mL tubes (3 tubes/treatment per sample day) amended with 1 mL buffer alone or buffer containing pine bark, quebracho, chestnut or mimosa tannins. Treatments achieved 0.63% (wt/wt) quebracho, chestnut or mimosa tannins in experiment 1, or 4.5% pine bark or 9% quebracho, chestnut or mimosa tannins in experiment 2. Tubes were inoculated with a novobiocin- and nalidixic acid-resistant Salmonella Typhimurium, closed with caps and incubated at successive 3-day increments at 22°C, 37°C and 42°C, respectively. In experiment 1, bacterial counts in contents collected on days 0, 6 and 9 revealed a treatment by day effect (P < 0.03), with the Salmonella challenge being 1.3 log10 CFU/g higher in quebracho-treated composts than in untreated controls after 6 days of composting. After 9 days of composting, Salmonella, wildtype Escherichia coli and total aerobes in untreated and all tannin-treated composts were decreased about 2.0 log10 CFU/g compared to day 0 numbers (3.06, 3.75 and 7.77 log10 CFU/g, respectively). Urea and ammonia concentrations tended (P < 0.10) to be increased in chestnut-treated composts compared to controls and concentrations of uric acid, urea and ammonia were higher (P < 0.05) after 9 days composting than on day 0. Despite higher tannin application in experiment 2, antibacterial effects of treatment or day of composting were not observed (P > 0.05). However, treatment by time of composting interactions were observed (P < 0.05), with quebracho- and chestnut-treated composts accumulating more uric acid after 24 h and 9 days of composting and chestnut-, mimosa- or quebracho-treated composts accumulating less ammonia than untreated composts. Results demonstrate that composting may effectively control pathogens and that tannin treatment can help preserve the crude protein quality of composting poultry litter.